Workforce Retention In Small Business : A Case Study Of Siti Fesyen,Tumpat,Kelantan. - Nor Azuani Mohamed Ariff. (2017)
Workforce retention meant a great deal to labour-intensive organization and businesses. Job satisfaction is cited to be positively related to workforce retention and plays an important role in ensuring that the workers stay in the organizations and in curbing turnover from occurring. There are elements and factors that will affect the job satisfaction and dissatisfaction. Ability to retain workers meant ability to manage your resources and cost. This paper looks into the factors and elements that affect the workers satisfaction and in turn their turnover and retention at Siti Fesyen. The data and information was collected using the interview and observation methods. The interviews were conducted with the founder, owner and a few workers, current and former workers of Siti Fesyen. The purpose of the interviews being to gather information on the business, the issues faced by the business and the workers, the engagement and satisfaction factors of the workers, the intention to leave,the reasons behind the tumover, and et cetera. The data and information gathered was then simplified, improved, analysed, discussed and interpreted to come up with the workers’ tumover rate and also retention rate. From the formula, the tumover rate of Siti Fesyen was 20%, higher than the 2013 national average of 13.2%, with the retention rate of 67%. Thus, the study helps to identify and discuss the factors and elements that relates to the workers intention to leave and recommend the measure to be taken to mitigate the risks and overcome the issues. The study also concluded that there is a positive relationship between workers satisfaction to workers retention or turnover.